2017
DOI: 10.3389/fpls.2016.01988
|View full text |Cite
|
Sign up to set email alerts
|

Frameshift Mutation Confers Function as Virulence Factor to Leucine-Rich Repeat Protein from Acidovorax avenae

Abstract: Many plant pathogens inject type III (T3SS) effectors into host cells to suppress host immunity and promote successful infection. The bacterial pathogen Acidovorax avenae causes brown stripe symptom in many species of monocotyledonous plants; however, individual strains of each pathogen infect only one host species. T3SS-deleted mutants of A. avenae K1 (virulent to rice) or N1141 (virulent to finger millet) caused no symptom in each host plant, suggesting that T3SS effectors are involved in the symptom formati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Previously, Lrp has been demonstrated to play a role in the virulence of some plant pathogens, including Xanthomonas spp. ( Cubero and Graham, 2004 ), Acidovorax avenae ( Kondo et al, 2017 ) and Erwinia amylovora ( Schachterle and Sundin, 2019 ). Similarly, our findings indicate critical roles of Lrp for P. stewartii with regard to capsule production, motility, growth, and virulence.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, Lrp has been demonstrated to play a role in the virulence of some plant pathogens, including Xanthomonas spp. ( Cubero and Graham, 2004 ), Acidovorax avenae ( Kondo et al, 2017 ) and Erwinia amylovora ( Schachterle and Sundin, 2019 ). Similarly, our findings indicate critical roles of Lrp for P. stewartii with regard to capsule production, motility, growth, and virulence.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, sequence analysis of regions flanking the transposons revealed that they were inserted into 68 different genes. In addition, multiple proteins were secreted by strains N1141 and K1 using their T3SS (Kondo et al, 2017;Kawaguchi et al, 2021). The presence of multiple effectors in A. avenae strains N1141 and K1 raises the question of whether NRHIF and KRHIF are the only ETI-inducible effectors for rice and finger millet, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Cultures of rice cells were grown at 30°C under light irradiation (Baba et al, 1986 week, and all experiments were performed 4 days after transfer. Acidovorax avenae N1141 (MAFF 301141), T3SS-deficient N1141 strain (NΔT3SS), K1 (MAFF 301755), and T3SS-deficient K1 strain (KΔT3SS) were used as previously described (Kadota et al, 1996;Che et al, 2000;Kondo et al, 2017). Rice (O. sativa L. subsp.…”
Section: Plants and Bacteriamentioning
confidence: 99%
See 1 more Smart Citation